Fetal hemifacial microsomia: understanding the phenotypic spectrum in a case report - Lacunza Paredes, Rommel Omar (2019)
Hemifacial microsomia involves a broad spectrum of facial malformations of varying severity. Prenatal diagnosis rarely occurs and is usually related to severe cases or associated with other body malformations. We present a case of severe hemifacial microsomia with multiple gastrointestinal and cerebral malformations.